PRELIMINARY GEOCHEMICAL AND SEDIMENTOLOGICAL ANALYSIS IN NW CORFU: THE MIOCENE SEDIMENTS IN AGIOS GEORGIOS PAGON - Tserolas, P.; Mpotziolis, C.; Maravelis, A.; Zelilidis, A. (Bulletin of the Geological Society of Greece, 2016)
A total of 80 samples of the Miocene deposits in Agios Georgios Pagon (NW Corfu) were selected and studied in regard of their geochemical and sedimentological characteristics. Organic content and calcium carbonate measurements were used and combined to investigate the depositional conditions and preliminary source rock potential. TOC analysis presented significant values ranging up to ~3% of organic carbon, with an average of 0,7%, and thus providing a promising basis for further assessment of their source rock potential. Calcium Carbonate measurements presented an average of ~27%. Fluctuations, correlative trends and the combined use of sieve analysis provide insights and alterations in the depositional conditions. The studied strata are part of an ongoing investigation throughout the Miocene to Pliocene sediment accumulations in Corfu, from Lefkimmi in the SW part to Agios Stefanos to the NW. The depositional conditions and source rock potential should provide new insights in understanding the geotectonic processes and basin development in the western margin of the Hellenic Fold and Thrust Belt.